IbM TUNA NETRA SUDARNO DAN SUPARDIONO DI KARANGANYAR - Isnaini Herawati; Wahyuni Wahyuni (WARTA LPM, 2015)
Today, a massage parlors have developed, including massage parlors by blind people. In Karanganyar, there are 9 massage parlors done by blind people under PERTUNI (Society for the Blind Indonesia), and the number was not included in the outposts or sub-districts in Karanganyar. There are two business units that will be a partner, namely Mr. Sudarno and Mr. Supardiono. This community service aims to increase the number of customers and to improve the quality of the Blind Massage services Sudarno and Supardiono. Activities that have been implemented are: the observation of the partners’ needs, fulfilling the needs of  partners, training on massage and aromatherapy, and improve promotional partner with signboards at strategic places. Partner 1 already has 3 pieces adequate massage booths, even one cubicle equipped with air conditioning. The first partners are still in need of help for marketing. Partner 2 requires repair his massage booths so as to provide convenience for customers.